Indigenous Peoples Batin Sembilan facing forest restoration pressure in Indonesia - Delfi, Maskota; Nurti, Yevita; Irwandi, Ade; Weintré, Johan (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2023)
his article aims to demonstrate the presence of the Batin Sembilan indigenous population in the Hutan Harapan area within the PT REKI (Ecosystem Restoration) concession in Jambi Province. The Batin Sembilan community's existence is a paradox amidst efforts to preserve the forest, which is facing a rapidly escalating rate of destruction and requires restoration. PT REKI-Hutan Harapan must not only focus on restoring the forest, but also on upholding the rights of the indigenous people residing within it. Ethnographic research conducted on the Batin Sembilan community, which continues to exist in the Hutan Harapan area, reveal the correlation between forest restoration and the sustenance of human existence inside it. The findings indicate that the Batin Sembilan population, who rely on forest resources, persistently endeavor to adjust to the constraints imposed by limited forest access. Hutan Harapan implements a comprehensive approach that includes resettlement, empowerment, and active involvement of the Batin Sembilan community in forest conservation activities. This strategy aims to ensure the long-term viability of the environment, which in turn has positive effects on both the livelihoods of the community and the fertility of the forest.